A review of analytical methods for the determination of hypericin in foods, herbal, biological and pharmaceutical matrices - de Araújo, Patricia Rocha [UNESP]; Fonseca-Santos, Bruno [UNESP]; Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2020)
Aims: A review of analytical methods for the determination of hypericin in foods, herbal, biological and pharmaceutical matrices. Background: Hypericin (HYP) is a naturally-occurring pigment obtained from some plants of the genus Hy-pericum. Although HYP has been known for many years, it has recently attracted attention due to its varied biological properties, such as anti-inflammatory and antidepressant activity and it is also an efficient photosensitizer. Objective: The objective of this review is to provide insights into the physicochemical properties of HYP, as well as to report the analytical methods existing in the literature and official compendia for different matrices. Methods: The survey data were collected by Google Scholar® and Scopus® using keys terms. Result: Analytical methods involving HYP are mainly concerned with the quality control of pharmaceutical preparations, foods, beverages, biological samples and drug delivery systems using different types of analysis methods. Some difficulties have also been identified due to the physicochemical properties of HYP. It presents great solubility in alkaline solutions, organic bases and common polar organic solvents. Conclusion: It can be analyzed by thin layer chromatography, spectrophotometry in the ultraviolet region, but the most commonly used method is by HPLC. HYP presents monographs in the American, British and European Pharmacopoeias, however, the methods of analysis are not yet harmonized.
Keywords: Analytical methods; Anti-inflammatory; Antidepressant; HPLC; Hypericin; Hypericum; Photosensitizing